Answer:
general rule
an = 51 - 3 (n - 1)
a20 = -6
Step-by-step explanation:
Looking at the first four terms of the series we see that each consecutive term is 3 less than the previous term. For example. 51 - 3 = 48, 48 - 3 = 45 and so on.
Therefore the general rule for the nth term is
![a_n=51-3(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/5gyf4e4y5devbxmctquyh4n9xcze1x4uts.png)
note that the use of using n - 1 is that when n = 1 we have
a_1 = 51 - 3(1-1) = 51 - 0 = 51
in other words, n - 1 helps us in setting a1 = 51.
Now once we have the general rule, we now find a20
![a_(20)=51-3(20-1)](https://img.qammunity.org/2023/formulas/mathematics/college/1aj38xdnbtisq0fvi5fbm3pk7noi74i25l.png)
which simplifies to give
![a_(20)=51-3\cdot19](https://img.qammunity.org/2023/formulas/mathematics/college/ruzmn28zbk2aeopkjeylf8do3f9gverqw7.png)
![\therefore a_(20)=-6](https://img.qammunity.org/2023/formulas/mathematics/college/bak8hk9cd62kqsdfaizrklw2fxczkqk8zm.png)
which is our answer!